PENGARUH KUALITAS PELAYANAN, TEMPAT, DAN HARGA TERHADAP KEPUASAN PELANGGAN STUDI KASUS ROTI BAKAR 88 PORIS JAYA, KOTA TANGERANG - Bastian, Asep Ferry; Aghata, Tessa Brillian; Sukaesih, Imas (Universitas Islam Syekh-Yusuf, 2020)
The purpose of writing this thesis is to determine the extent of the relationship between Service Quality (X1), Place (X2), and Price (X3) on Customer Satisfaction (Y) at Roti Bakar 88 Poris Jaya, Tangerang City. The research method used was through the distribution of google form questionnaires to respondents as visitors to Roti Bakar 88, as well as a literature review used as secondary data. For the analysis of this research the author uses quantitative analysis methods. The results of the analysis are obtained by the following calculations: from the results of multiple linear analysis obtained Y = 22.034 + 0.224 X1 + 0.18 X2 + 0.318 X3 + 5.366 means that there is an increase and decrease between the variables X1, X2, and X3 then customer satisfaction will experience an increase and decrease. From the results of the coefficient of determination (R2) the influence of service quality, place, and price of each variable affects customer satisfaction by 18.9%, the rest is influenced by other factors. Based on the results of hypothesis testing, it is obtained that tcount for the influence of service quality is 2,910, tcount for the influence of place is 0.259, and tcount for the effect of price is 3.616 which is obtained from the distribution ttable for df = n - k = 100 - 4 and the level of significance is 0.05 then it is found that ttable is 1.984. In other words, H1 and H3 are accepted while H2 is rejected, because tcount > ttable.